Functional Outcomes Post Lisfranc Injury—Transarticular Screws, Dorsal Bridge Plating or Combination Treatment?. Issue 8 (August 2017) - Lau, Simon; Guest, Catherine; Hall, Marcus; Tacey, Mark; Joseph, Samuel; Oppy, Andrew
Abstract : Objective: To identify whether transarticular screws, dorsal bridging plates or a combination of the 2 result in the best functional outcome after Lisfranc injury. Design: Case series. Setting: Level one trauma center. Patients: Fifty patients who underwent surgical fixation of Lisfranc injuries over a 6-year period were retrospectively reviewed. Intervention: One of 3 treatment arms: transarticular screw fixation alone, dorsal bridge plating alone or a combination of dorsal bridge and transarticular screw fixation. Main Outcome Measures: The primary outcome measures were 1 of 2 midfoot scores—the American Orthopaedic Foot and Ankle Society (AOFAS) Midfoot Score and the Foot Function Index (FFI) Score. Secondary results included postoperative complications. Results: Quality anatomical reduction is the best predictor of functional outcomes (FFI— P = 0.008, AOFAS— P = 0.02). Functional outcomes with both FFI and AOFAS scores were not significantly associated with any of the fixation groups (FFI— P = 0.495, AOFAS— P = 0.654) on univariate analysis. Injury type by Myerson classification systems or open versus closed status was also not significantly associated with any fixation group. Open exposures were more likely to result in soft-tissue complications, but there was no significant difference in metalware failure or need for removal. Conclusion: Functional outcomes after Lisfranc fractures are most dependant on the quality of anatomical reduction and not the choice of fixation implant used. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.